Speech disfluencies in Parkinson’s disease - Półrola, Paweł J.; Góral-Półrola, Jolanta (Medical Studies/Studia Medyczne, 2015)
Introduction : Even though speech disfluency is listed in the clinical description of Parkinson’s disease (PD), its nature, intensity, symptomatology, and the effect on verbal communication have not hitherto been defined. Aim of the research: The research paper presents the results of studies aimed at the description of speech disfluencies in PD and the influence on verbal communication. Material and methods : The tests involved 10 patients from 54 to 72 years of age with documented PD, responsive to L-dopa preparations. The principal method of the study was based on the linguistic analysis of the utterances produced by the people with PD. Results: The intensity of the speech disfluency observed in the utterances of persons with PD ranged from 6.6% to 23.0%, so it was significantly higher than that which is assumed as acceptable (3–5%); the speaking rate of the examined persons ranged from 0.7 syllabes (syl.)/s to 4.0 syl./s, and only 2 examined persons spoke with a rate considered to be correct (4–6 syl./s). This demonstrates that speech disfluency is a communication barrier in PD. Conclusions : The absence of differentiation in the speech disfluency (SD) severity between different types of verbal utterances (difference not statistically significant) and a specified hierarchy of SD symptoms indicate that the speech disfluency in PD has an essentially organic background and is generated by cognitive, linguistic, and motor deficits resulting from the damage to the central nervous system. This is also confirmed by the established hierarchy of utterances with respect to the SD intensity, not excluding the simultaneous participation of the emotional factor.